2015
DOI: 10.1182/blood-2014-12-618892
|View full text |Cite
|
Sign up to set email alerts
|

Dicer1 imparts essential survival cues in Notch-driven T-ALL via miR-21–mediated tumor suppressor Pdcd4 repression

Abstract: Key Points Dicer1-mediated miRNA biogenesis is essential for induction and maintenance of Notch1-driven T-ALL. miR-21 regulates survival of T-ALL, in part through the repression of the tumor suppressor gene Pdcd4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 67 publications
(90 reference statements)
0
22
0
Order By: Relevance
“…Microarray-based miRNA profiling revealed that miR-21 was deregulated in mouse and human T-ALL cells. Furthermore, miR-21 was shown to regulate T-ALL cell survival via repression of the tumor suppressor PDCD4 (46). In addition, the tumor suppressor Spry2 was revealed to be negatively correlated with miR-21 expression in myeloma cells.…”
Section: Mir-21 and Hematological Malignanciesmentioning
confidence: 98%
“…Microarray-based miRNA profiling revealed that miR-21 was deregulated in mouse and human T-ALL cells. Furthermore, miR-21 was shown to regulate T-ALL cell survival via repression of the tumor suppressor PDCD4 (46). In addition, the tumor suppressor Spry2 was revealed to be negatively correlated with miR-21 expression in myeloma cells.…”
Section: Mir-21 and Hematological Malignanciesmentioning
confidence: 98%
“…Junker et al showed that the leukemia onset of this mouse model is dependent on Dicer1 -mediated biogenesis of miRNAs [101]. When HPCs with ICN1 overexpression were injected in conditional Dicer1 knockout mice, where Dicer1 is inactivated when thymocytes or leukemic cells transit from the double negative to double positive (CD4 + CD8 + ) stage, there was no leukemic onset compared with control mice that all developed leukemia in less than 100 days.…”
Section: Methodological Approaches In Mirna and Long Noncoding Rna Rementioning
confidence: 99%
“…To further confirm the function of miR-21, we tested the protein levels of PTEN (phosphatase and tensin homolog deleted on chromosome ten) and PDCD4 (programmed cell death protein 4), which were the target genes of miR-21 ( Junker et al, 2015;Xu et al, 2015). The data showed that miR-21 suppressed the protein levels of PTEN and PDCD4, and the protein levels of PTEN and PDCD4 decreased apparently at ratios RNAiMAX:miR-21 = 3:5, 4:5, 5:5 (Fig.…”
Section: Protein Levels Of Pten and Pdcd4mentioning
confidence: 99%